Efficient Synthesis of Large Finite Patch Arrays for Scanning Wide-Angle Anomalous Reflectors - Sravan Kumar Reddy Vuyyuru; Risto Valkonen; Sergei A. Tretyakov; do-Hoon Kwon (IEEE Open Journal of Antennas and Propagation)
A design methodology for planar loaded antenna arrays is proposed to synthesize a perfect anomalous reflection into an arbitrary direction by optimizing the scattering characteristics of passively loaded array antennas. It is based on efficient and accurate prediction of the induced current distribution and the associated scattering for any given set of load impedances. For a fixed array of finite dimensions, the deflection angles can be continuously adjusted with proper tuning of each load. We study and develop anomalous reflectors as semi-finite (finite infinite) and finite planar rectangular arrays comprising printed patches with a subwavelength spacing. Anomalous reflection into an arbitrary desired angle using purely reactive loads is numerically and experimentally validated. Owing to the algebraic nature of load optimization, the design methodology may be applied to the synthesis of large-scale reflectors of practical significance.